Influência da composição química foliar na colonização por larvas de Chironomidae (Diptera) durante a decomposição em riachos - Rossi, Luciene Aparecida Leite (2016)
With the purpose of elucidating some aspects concerning the influence of leaf chemical composition on Chironomidae (Diptera) larvae colonization and their role in decomposition, field experiments were carried out here presented in four chapters: i) Chemical and elemental composition of leaf litter of Hedychium coronarium, Pteridium arachnoideum and Magnolia ovata during decomposition in a low-order stream; ii) Influence of leaf chemical composition in the colonization of Hedychicium coronarium, Pteridium arachnoideum and Magnolia ovata leaf litters by Chironomidae (Diptera) larvae; iii) Feeding habits of the Chironomidae (Diptera) larvae and their contribution to the consumption of plant tissues during decomposition in low order streams; iv) Influence of Chironomidae (Diptera) larvae in the kinetics of aerobic decomposition of Hedychium coronarium, Pteridium arachnoideum and Magnolia ovata leaf litters. The experiments were performed in low order streams in São Carlos-SP and consisted on incubation of polyethylene bottles with small holes containing dried leaves of the three plant species, being removed from time to time over 85 days. Overall, the results indicated that: i) the invader leaf litter showed major quantities of refractory and allelopathic materials than native one; ii) differences in the leaf litter chemical composition influenced the Chironomidae larvae colonization; iii) the chironomids feeding habits differed among plant species and vary with the time of incubation of the leaf litter, amount of remaining mass and adhered organic matter; iv) Chironomidae larvae, mainly shredders, that colonize leaf litters can influence mass loss.